Eksistensi Bawaslu Kabupaten Sukoharjo dalam Pengawasan Pemilihan Umum - Fernando, Henokh; Natalia, Devita; Ochtawiaji, Farid; Arianti, Leni; Fitriyan, Selvina (Journal of Contemporary Law Studies, 2024)
The purpose of this study is to examine the role and authority of Bawaslu in Sukoharjo Regency in supervising the 2024 General Elections to ensure a democratic and fraud-free election process. This study employs an empirical juridical method, focusing on the application or implementation of normative legal provisions in legal events occurring within Bawaslu Sukoharjo Regency. The results indicate that Bawaslu Sukoharjo Regency plays a strategic role in overseeing all stages of the election process, from planning, implementation, to post-election stages. This authority is governed by Law No. 7 of 2017 on General Elections, Law No. 22 of 2007 on Election Organizers, and Bawaslu Regulation No. 13 of 2022 on Procedures for Election Supervision. In conclusion, Bawaslu Sukoharjo Regency plays a crucial role in maintaining the integrity and transparency of the election process. Through effective supervision, Bawaslu can prevent and address violations and fraud, thereby supporting the realization of a democratic and fair government.